2021
DOI: 10.3389/fonc.2021.621060
|View full text |Cite|
|
Sign up to set email alerts
|

Fragile Gene WWOX Guides TFAP2A/TFAP2C-Dependent Actions Against Tumor Progression in Grade II Bladder Cancer

Abstract: IntroductionThe presence of common fragile sites is associated with no-accidental chromosomal instability which occurs prior to carcinogenesis. The WWOX gene spans the second most active fragile site: FRA16D. Chromosomal breakage at this site is more common in bladder cancer patients who are tobacco smokers which suggests the importance of WWOX gene loss regarding bladder carcinogenesis. Tryptophan domains of WWOX are known to recognize motifs of other proteins such as AP-2α and AP-2γ allowing protein-protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 96 publications
(121 reference statements)
4
27
0
Order By: Relevance
“…Mitochondrial redox potential indicates cell viability; this assay was analyzed as described previously [8], i.e., the variant was considered meaningful if at least three measurement points met statistical significance. Thus, HT-1376 cell viability decreased after WWOX overexpression (mean 1.12-fold) but increased after AP-2γ overexpression (mean 1.16-fold).…”
Section: Wwox Ap-2α and Ap-2γ Were Diversely Localized Depending On The Cellular Variantmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial redox potential indicates cell viability; this assay was analyzed as described previously [8], i.e., the variant was considered meaningful if at least three measurement points met statistical significance. Thus, HT-1376 cell viability decreased after WWOX overexpression (mean 1.12-fold) but increased after AP-2γ overexpression (mean 1.16-fold).…”
Section: Wwox Ap-2α and Ap-2γ Were Diversely Localized Depending On The Cellular Variantmentioning
confidence: 99%
“…It was found that both WWOX and AP-2α hinder cancer progression and may act synergistically. In contrast, AP-2γ supports tumor development, but its action may be diminished by WWOX, resulting in a net anti-tumor effect [8]. Nonetheless, the conclusion of previous work was based on grade 2 (G2) bladder carcinoma; hence, profound examination is advisable on higher grades of BLCA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…6e). WWOX is within a known fragile site and has been reported in several studies of different tumor types including breast, prostate, lung, esophagus, cervical, ovarian and bladder cancers [57][58][59][60][61].…”
Section: Putative Driver Candidates Identified At Significantly Recurrent Peaks In Bppcmentioning
confidence: 99%
“…Oncology research includes the discovery of novel tumor suppressor genes and investigations of their roles in the development of tumors (7). Common fragile sites (CFS) are site-specific unstable regions in the normal genome and include the rare fragile sites (8). While the role of rare fragile sites in tumors remains unclear, CFS is consistent for many tumor genome mutations, and they are closely related to the occurrence and development of tumors (9).…”
Section: Introductionmentioning
confidence: 99%